Cinical and pathological characteristics of Chinese patients with antineutrophil cytoplasmic autoantibody associated systemic vasculitides: a study of 426 patients from a single centre. Issue 961 (4th November 2005) - Chen, M; Yu, F; Zhang, Y; Zhao, M H
Abstract : Background: Antineutrophil cytoplasmic autoantibodies (ANCA) are serological markers of ANCA associated systemic vasculitides (AASV), which is one of the most common multisystem autoimmune diseases. Features of Chinese patients with AASV have not been fully investigated. Objective: To analyse the clinical and pathological characteristics of Chinese patients with AASV. Methods: 426 Chinese patients with AASV diagnosed in the past eight years were retrospectively studied and their clinical and pathological data were analysed. Results: Of the 426 patients, 87 (20.4%) were Wegener's granulomatosis, 337 (79.1%) were microscopic polyangiitis and two (0.5%) were Churg-Strauss syndrome. Only 201 of 426 (47.2%) patients were diagnosed within three months. Clinically, the patients had multisystem involvement. Altogether 371 of 426 (87.1%) had kidney involvement and 260 of 426 (61.0%) had lung involvement. The prevalences of renal involvement and fatigue were significantly higher in patients with MPO-ANCA than that in patients with PR3-ANCA; the prevalences of ophthalmic, nasal involvement, rash, and arthragia were significantly higher in patients with PR3-ANCA than those in patients with MPO-ANCA. The one and five year death rates were 13.1% and 22.4%, respectively. The percentage of patients progressing to end stage renal disease at one and five years was 15.9% and 27.1%, respectively. Conclusions: AASV is not a rare autoimmune disease in Chinese people. Kidney and lung were the most vulnerable organs. For patients with multiorgan damage, an ANCA test should be performed to make an early diagnosis and to start treatment in time.